Penerapan Media Dart Board Untuk Meningkatkan Hafalan Pada Materi Al-Qur’an Hadist Kelas IV MI Plus Ma’arif NU Bacem Ponggok Blitar - Yuli Al Manik, Siti Khumairo'; Farida, Rista (Institut Agama Islam Riyadlatul Mujahidin Ngabar (IAIRM) Ponorogo, 2023)
Abstrak This research aims to evaluate the use of Dart Board media in improving memorization of short letters and hadiths in Al-Qur'an Hadith lessons at MI Plus Ma'arif NU Bacem Ponggok Blitar. Positive research results show students' high interest in the Dart Board, creating comfort in repeating the material, and is considered fun. Even though some students reject this media due to lack of mastery of the material, this provides an opportunity to improve the delivery of material by teachers. The process of making a dartboard involves selecting materials, forming circles at a certain distance, cutting the pattern manually, and arranging the pattern on a sponge base using glue as an adhesive. The Dart Board contains numbers with pieces of verses from the Koran and Hadith, allowing students to answer questions related to the material when throwing darts. The steps for using the Dart Board involve explaining learning objectives, dividing groups, creating a table for calculating points, distributing darts, determining turns, throwing darts, and answering questions from cards. Research shows an increase in students' memorization through repeated practice with the Dart Board. The results of the research also include class IV material, including the letters al-'Asyr, al-Qurays, al-Ma'un, at-Takasur, as well as hadiths about the Taqwa of Tirmidhi's History and hadiths about the Intentions of Bukhari's History. It is hoped that the Dart Board can become a strategic learning tool to improve memorization and understanding of Al-Qur'an Hadith material by providing satisfaction and interest for students. Keywords: Instructional Media, Dart Board, Improving Memorization Penelitian ini bertujuan untuk mengevaluasi penggunaan media Dart Board dalam meningkatkan hafalan surat pendek dan hadist pada pelajaran Al-Qur'an Hadist di MI Plus Ma’arif NU Bacem Ponggok Blitar. Hasil positif penelitian menunjukkan minat tinggi peserta didik terhadap Dart Board, menciptakan kenyamanan dalam mengulang materi, serta dianggap menyenangkan. Meskipun sebagian peserta didik menolak media ini akibat kurangnya penguasaan materi, hal ini memberikan peluang untuk peningkatan penyampaian materi oleh guru. Proses pembuatan papan dart melibatkan pemilihan bahan, pembentukan lingkaran dengan jarak tertentu, pemotongan pola secara manual, dan penyusunan pola di atas dasar spons menggunakan lem sebagai perekat. Dart Board berisi angka dengan potongan ayat Al-Qur'an dan Hadis, memungkinkan peserta didik menjawab pertanyaan terkait materi saat melempar panah. Langkah-langkah penggunaan Dart Board melibatkan penjelasan tujuan pembelajaran, pembagian kelompok, pembuatan tabel untuk penghitungan poin, pembagian panah, penentuan giliran, lemparan panah, dan penjawaban pertanyaan dari kartu. Penelitian menunjukkan peningkatan hafalan peserta didik melalui latihan berulang dengan Dart Board. Hasil penelitian juga mencakup materi kelas IV, termasuk surat al-'Asyr, al-Qurays, al-Ma'un, at-Takasur, serta hadis tentang Taqwa Riwayat Tirmidzi dan hadis tentang Niat Riwayat Bukhari. Dart Board diharapkan dapat menjadi sarana pembelajaran strategis untuk meningkatkan hafalan dan pemahaman materi Al-Qur'an Hadis dengan memberikan kepuasan dan ketertarikan bagi peserta didik. Kata Kunci: Media Pembelajaran, Dart Board, Peningkatan Hafalan